Laser 3D printing of CoCrFeNiAlx high entropy alloys - Ooi, Hsu Chien (2017)
Metal three-dimensional (3D) printing, formally known as metal additive manufacturing (AM), has been gaining a lot of attention recently because it is now feasible to completely print fully dense and functional parts. The improvements in manufacturing accuracy, surface finish and the ability to produce parts with complex and intricate details give metal printing great advantages over conventional subtractive and formative technologies. However, the prevailing issues with metal 3D printing are the limited range of materials available and the high cost of metal powders. The aim of this project is to explore the feasibility of achieving a homogenous mixture of the CoCrFeNiAlx (x=0.1, 0.5 and 1.0) high entropy alloys (HEAs) by blending elemental powder of Al with pre-alloyed CoCrFeNi base powder. This project also aims to study the effects of proportions of Al on the microstructure and mechanical properties of CoCrFeNiAl0.1, CoCrFeNiAl0.5 and CoCrFeNiAl1.0 samples printed using selective laser melting (SLM). The CoCrFeNiAl0.5 samples showed good printability and improvements in microhardness and tensile properties with a reduction in density. However, the CoCrFeNiAl0.1 samples suffered from a large number of thermal cracks and consequently showed a decline in mechanical properties. The CoCrFeNiAl1.0 samples had large cracks that propagated throughout the samples, indicating its poor laser printability. Therefore, further studies are needed to optimize the SLM printing parameters for the CoCrFeNiAl0.1 and CoCrFeNiAl1.0 powders.